Effect of Lactic Acid Bacteria Concentration on Modification of Banana Weevil Flour by Fermentation: Pengaruh Konsentrasi Bakteri Asam Laktat terhadap Modifikasi Tepung Bonggol Pisang Secara Fermentasi - Gunawan, Sito Luthfi; Hamid, H (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Banana weevil is a waste that has not been used much, however banana weevil has content lots of nutrition . So that need effort for utilise the banana weevil so that it can beneficial for society . This study used lactic acid bacteria fermentation method which aims to analyze the characteristics of modified banana weevil flour. Then thinly sliced banana weevil soaked for 2 hours inside sodium metabisulfite solution then soaked again use finished solution mixed with bacteria sour lactate with concentration 0;0,02;0,025;0,03 ml/L. After that hump dried and ground for become flour and tested characteristics . The results showed that the swelling power test level was highest at a concentration of 0.03 ml/L, which was 13.39 grams, the % solubility test was highest at a concentration of 0.03 ml/L with a value of 0.12%, the results of the viscosity test after being modified had the same value, namely of 1.4 mPa.s, for the results of reducing sugar content after being modified it decreased and a result of 4% was obtained.